1986
DOI: 10.2307/352578
|View full text |Cite
|
Sign up to set email alerts
|

Black Husbands' Satisfaction with Their Family Life

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…For example, well-educated men were found to endorse less traditional gender role beliefs than less educated men (Long & Graham, 1991), and well-educated fathers with more prestigious occupations and greater family income were more involved (Volling & Belsky, 1991). Education level and income of the household were also found to be significant predictors of perceived family life satisfaction among African American husbands (Ball & Robbins, 1986). The results of this study support the earlier findings regarding the relationship between income, education level, and satisfaction with life (Diener, 1984).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…For example, well-educated men were found to endorse less traditional gender role beliefs than less educated men (Long & Graham, 1991), and well-educated fathers with more prestigious occupations and greater family income were more involved (Volling & Belsky, 1991). Education level and income of the household were also found to be significant predictors of perceived family life satisfaction among African American husbands (Ball & Robbins, 1986). The results of this study support the earlier findings regarding the relationship between income, education level, and satisfaction with life (Diener, 1984).…”
supporting
confidence: 87%
“…For example, both earlier (Diener, 1984) and recent reviews of literature (Lyubomirski, King, & Diener, 2005) suggested that income and education level are positively related to satisfaction with life and happiness. Another study by Ball and Robbins (1986) revealed that demographic factors such as education level and income of the household were significant predictors of perceived family life satisfaction in African American husbands. Educated men were found to hold less traditional gender role beliefs than less educated men (Long & Graham, 1991), and fathers with less traditional gender role beliefs were more involved in childrearing (Beitel & Parke, 1998).…”
mentioning
confidence: 97%
“…The more individuals dislike their lives in general, their marriage, their job, or other major life roles, the worse may be their health status; on the other hand, the better off individuals perceive their life aspects, the better their health status. Ball and Robbins (1986) noted that numerous studies have demonstrated happiness has a positive correlation to health status. Thus, identification of the manner in which various aspects of individuals' lives contribute to global life happiness and well-being can be quite significant.…”
Section: Implications For Policy and Practicementioning
confidence: 96%
“…While there has been little research conducted in the area of marital and family satisfaction in the African American family, it has been shown that factors such as income, sex, age, education, available social support network, parental status, and marital status affect the levels of satisfaction within marriage and the family in general (Broman, 1988b;Ellison, 1990;Ball and Robbins, 1986). Income level has been cited as an important factor in marital satisfaction and stability (Collins, 1988;Heaton and Albrecht, 1991).…”
Section: Marital Relationsmentioning
confidence: 99%
“…Among older couples, the wife's satisfaction is lower when she is employed and the husband is not (Lee, 1988). Ball and Robbins (1986) conducted a study to examine the degree of marital satisfaction reported by a sample of 158 southem African American husbands of various socioeconomic levels. They found that husbands in families with greater per capita financial resources tend to be more satisfied with their family lives than those with fewer resources.…”
Section: Marital Relationsmentioning
confidence: 99%